Actors’ logics concerning municipal integration policies for refugees in North Rhine-Westphalian cities and small towns - Adam, Francesca; Föbker, Stefanie; Imani, Daniela; Pfaffenbach, Carmella; Weiss, Günther; Wiegandt, Claus-Christian (Raumforschung und Raumordnung | Spatial Research and Planning, 2019)
With the significant increase in immigration of refugees since the mid-2010s, cities and municipalities are facing new challenges of social integration with their local policies on foreigners and migration. These challenges are handled through the interaction of various, in part new, local actors from the public sector (e.g. municipal administration, welfare organisations), the commercial sector (e.g. employers) and the civil society (e.g. voluntary initiatives). In this paper, the different logics of central actors involved in the integration processes are examined in order to show who creates and controls the local integration conditions under which preconditions. The study was conducted in two different local contexts, the city of Cologne and the district of Heinsberg, with the aim of highlighting differences and similarities in local governance. The results are based on 29 expert interviews with representatives of the city administrations, the civil society and experts of the state level who are involved in the integration process of refugees due to their professional or voluntary work. Different logics can be identified. Firstly, this applies to the relationship between state actors at the federal and state levels and local actors. Secondly, this also applies to the relationship between municipal and civil society actors. The spatial and situational contexts play a differentiating role.
Keywords: Refugees; Municipal integration policies; Governance; Cologne; District of Heinsberg